Changes of the eel fishery patterns in the Vistula Lagoon, Poland - I. Psuty; B. Draganik (Acta Ichthyologica et Piscatoria, 2008)
Background. The decline in the eel population is reflected in the decreased incomes of fishers. This has led to changes in the structure and size of the fishing effort. The fyke nets used in eel catches are multi-species gear. Changes in the fishing intensity and location of this gear impacts local fish resources, as does changing preferred gear for other types. Materials and methods. The data on the eel landings and the numbers of licences from all the fisheries bases were obtained from the Regional Sea Fisheries Inspectorate. Direct observations of the spatial and temporal deployment of the fishing effort was observed monthly in the 2000–2007 period. The trends of changes in relative eel abundance were identified from fyke net complexes deployed in the eastern fishing grounds. Results. Landings and directed fishing effort differed both seasonally and spatially. The most effective fishing grounds were in the eastern (near the border with Russia) and western parts of the lagoon. The discontinuation of stocking resulted in decreased catches and then in fishing effort. Decreases in eel catches and fishing efficiency were evident except in 2003 at the Piaski and KÄ…ty Rybackie fisheries bases (the northern part of the lagoon). Conclusion. The availability of eel stocks had the greatest impact on fishing efficiency and gear distribution patterns. The reduction of fyke net fishery because of low incomes shifted the focus of the fishery to gill nets targeting pikeperch.